Implementation of Reality Counseling to Overcome Self Regulation in Students with Broken Homes - Afifah; Netrawati; Zadrian Ardi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Reality counseling approach, reality counseling is self-regulation, and the impact of broken home families on students. It is an approach that focuses on the present and guides the counselee to face the reality of his life. The goal is to facilitate the counselee to achieve autonomy by taking responsibility for their decisions and actions. Techniques used include role-playing, humor, therapeutic confrontation, creation of a change plan, and affirmation of counseling boundaries. Self-regulation refers to the ability to manage thoughts, emotions, and behaviors to achieve desired goals. It involves the process of setting standards, conducting self-observation and evaluation, adjusting reactions to oneself, and conducting regular self-reflection. Self-regulation helps to increase students' independence, manage emotions, improve concentration, and build resilience and adaptability in different situations. A broken home family is a situation where there is disharmony between parents, which can be due to divorce, death of one of the parents, or other problems. The impact on students includes academic problems, behavior, sexual problems, and a greater need for emotional support. Counselors play an important role in helping students from broken homes to overcome their emotional challenges, build safe relationships, and provide the necessary support for self-regulation.